Effect of phytase from aspergillus niger on plant growth and mineral assimilation in wheat (Triticum aestivum Linn.) and its potential for use as a soil amendment - Gujar, Pradnya D.; Bhavsar, Kavita P.; Khire, Jayant Malhar (Journal of the Science of Food and Agriculture, 2013)
Background Extensive use of non-replenishable phosphate reserves as phosphate supplements in agriculture and animal feed poses a threat for environmental pollution and necessitated a search for alternative phosphate sources. Unlocking the phytate phosphorus using microbial phytase can provide an ecofriendly solution in agriculture. The aim of the present work was to evaluate the effect of phytase from Aspergillus niger NCIM 563 in degradation of phytate phosphorus to benefit plant nutrition and soil amendment in comparison with chemical fertilizers. Results An enzyme dose of 12 IU was sufficient to hydrolyze phytate and increase assimilation of phosphorus by about 74%. Phytase supplementation leads to increase in shoot:total length ratio by about 200%, indicating its growth-promoting effect. Consistency in phytase-induced growth was reflected at pot and tray levels, wherein shoot:total length ratio was observed to be 2.01 and 2.12 respectively. Mineral assimilation due to phytase was more efficient as compared to chemical fertilizers, thus overcoming the constraints of practicability and economics in the agriculture industry. Phytase was efficient in reducing the phytic acid content of soil by about 30% while simultaneously increasing the phytate phosphate availability by 1.18-fold. Conclusion Phytase from A. niger showed improvement in phytate phosphorus and mineral availability. Besides a plant growth-promoting effect, reduction in use of chemical fertilizers and soil improvement could be achieved simultaneously for maintaining the sustainability of agriculture. (c) 2012 Society of Chemical Industry
Keywords: mineral assimilation; Phytase; phytate degradation; plant growth promotion; soil amendment